Seroprevalence of Toxoplasma gondii in dogs in the province of Kocaeli - Simşek, Sami; Utük, Arma?an Erdem; Babür, Cahit; Köro?lu, Ergün (My University, 2006)
The aim of this study was to investigate the seroprevalence of Toxoplasma gondii in pet dogs and stray dogs in Kocaeli province using the Sabin-Feldman Dye Test. A total of 116 dogs were examined and 81 (69.8%) were found to be positive. Seropositivity was found to be 59.6% in male dogs and 78.1% in female dogs (p<0.05). Seropositivity was 62.5% in pet dogs and 71.7% in stray dogs (p>0.05). The seropositivity was found to be 68.2%, 75.6% and 62.5% in the 0-1, 1-3, and over 3 age groups, respectively. As a result, the high seropositivity of dog toxoplasmosis in Kocaeli province has been found to be important.
Kocaeli yöresi köpeklerinde Toxoplasma gondii seroprevalansi
Keywords: Age Distribution; Animals; Antibodies, Protozoan; Dog Diseases; Dogs; Female; Male; Seroepidemiologic Studies; Sex Distribution; Toxoplasma; Toxoplasmosis, Animal; Turkey; protozoon antibody; age distribution; animal; animal parasitosis; article; blood; dog; dog disease; epidemiology; female; immunology; male; sex ratio; Toxoplasma; Turkey (republic)